Intestinal Transcriptome Analysis Reveals Soy Derivative-Linked Changes in Atlantic Salmon - Kiron, Viswanath; Park, Youngjin; Siriyappagouder, Prabhugouda; Dahle, Dalia; Vasanth, Ghana K.; Dias, Jorge; Fernandes, Jorge M. O.; Sørensen, Mette; Trichet, Viviane Verlhac (Frontiers in Immunology, 2020)
Intestinal inflammation in farmed fish is a non-communicable disease that deserves attention because it is a major issue linked to carnivorous fishes. The current norm is to formulate feeds based on plant-derived substances, and the ingredients that have antinutritional factors are known to cause intestinal inflammation in fishes such as Atlantic salmon. Hence, we studied inflammatory responses in the distal intestine of Atlantic salmon that received a feed rich in soybean derivatives, employing histology, transcriptomic and flow cytometry techniques. The fish fed on soy products had altered intestinal morphology as well as upregulated inflammation-associated genes and aberrated ion transport-linked genes. The enriched pathways for the upregulated genes were among others taurine and hypotaurine metabolism, drug metabolism - cytochrome P450 and steroid biosynthesis. The enriched gene ontology terms belonged to transmembrane transporter- and channel-activities. Furthermore, soybean products altered the immune cell counts; lymphocyte-like cell populations were significantly higher in the whole blood of fish fed soy products than those of control fish. Interestingly, the transcriptome of the head kidney did not reveal any differential gene expression, unlike the observations in the distal intestine. The present study demonstrated that soybean derivatives could evoke marked changes in intestinal transport mechanisms and metabolic pathways, and these responses are likely to have a significant impact on the intestine of Atlantic salmon. Hence, soybean-induced enteritis in Atlantic salmon is an ideal model to investigate the inflammatory responses at the cellular and molecular levels.